42.2k views
4 votes
Express the following in the form ax2+bx+c=0:

(x+3)(3x - 2)=(4x +5)(2x-3)
(3x+2)^2=(x+2)(x-3)
(x+1)(x+2)=(2x-1)(x-2)

2 Answers

2 votes

Final answer:

To express the given equations in the form ax^2+bx+c=0, expand the products on both sides and then rearrange the terms. The equations become 8x^2 - 26x + 21 = 0, 8x^2 + 13x + 10 = 0, and x^2 + 2x = 0.

Step-by-step explanation:

To express the given equations in the form ax^2+bx+c=0, we can expand the products on both sides of the equation and then rearrange the terms. Let's take each equation one by one:

  1. (x+3)(3x - 2)=(4x +5)(2x-3)
    Expanding both sides:
    3x^2 - 2x + 9x - 6 = 8x^2 - 12x + 10x - 15
    Simplifying:
    11x - 6 = 8x^2 - 2x - 15
    Moving all terms to one side:
    8x^2 - 15x - 11x + 6 + 15 = 0
    Combining like terms:
    8x^2 - 26x + 21 = 0
  2. (3x+2)^2=(x+2)(x-3)
    Expanding the left side:
    9x^2 + 12x + 4 = x^2 - 3x + 2x - 6
    Combining like terms:
    9x^2 + 12x + 4 = x^2 - x - 6
    Moving all terms to one side:
    9x^2 - x^2 + 12x + x + 4 + 6 = 0
    Combining like terms:
    8x^2 + 13x + 10 = 0
  3. (x+1)(x+2)=(2x-1)(x-2)
    Expanding both sides:
    x^2 + 2x + x + 2 = 2x^2 - 4x - x + 2
    Simplifying:
    x^2 + 3x + 2 = 2x^2 - 5x + 2
    Moving all terms to one side:
    2x^2 - x^2 + 5x - 3x + 2 - 2 = 0
    Combining like terms:
    x^2 + 2x = 0

User Peaceful James
by
5.4k points
4 votes
Picture under is the answer for thisquestion
Express the following in the form ax2+bx+c=0: (x+3)(3x - 2)=(4x +5)(2x-3) (3x+2)^2=(x-example-1
User Monstieur
by
5.5k points